A comparative analysis of solid waste management in developed, developing and lesser developed countries. Issue 1 (1st January 2016) - Owolabi, Sunday A.; Mmereki, Daniel; Baldwin, Andrew; Li, Baizhan
Abstract : Solid waste (SW) management is a challenge across the globe due to the increasing diversity of waste characteristics and lack of effective implementation of consistent waste policies accompanied by changing lifestyles, increased production processes and rapid urbanization. To date, fewer papers have been published in international literature on a comparative analysis of SW management in developed, developing and lesser developed countries. To fill that gap, this comparative review aims to analyse SW management pratices in lesser developed, developing and developed countries, using existing data from 2005 to 2015, from major scientific journals, Waste Management; Resources, Conservation and Recycling; Journal of Environmental Management and Waste Management and Research, covering both quantitative and qualitative data to draw experiences from developed countries for improving SW management efficiency in lesser developed and developing countries. The findings from the comparative review indicate that SW management in lesser developed and developing countries is not well established and inefficient. Key issues were identified around lack of cooperation among stakeholders, institutional structural weaknesses, lack of legislated recycling, ad hoc and uncoordinated approaches. This paper provides the critical aspects that could be useful to policy- and decision-makers when developing, designing, and making adjustments and implementing efficient SW management systems in developing and lesser developed countries.